drawing perform’s: An Artistic research - Karna Mustaqim (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
The determination of academic research on the field of the arts education troubling its own artistic practices. It was assumed by clarifying the objective and method of doing the research, art was believed would be contributing to a greater intellectualisation, otherwise it is just an art practice without justification from science, and therefore no contribution worth to human knowledge. Since it contrastive to the nature of artistic practice embodied in the arts itself, which unfortunately not even realize by the artist his/herself. Whilst it is well said by Joseph Kosuth (1971) that: “the artist, not unlike a scientist for whom there is no distinction between working in the laboratory and writing a thesis, has now “to cultivate the conceptual implications of his art propositions, and argue their explication.” This paper is about explicating the writer as the artist himself who done the livedexperience of drawing performs as the research processed. Artists use drawings an activity or a way of understanding the meaning of who we are and how we lived in the world. However, the objective of this research is an exceptional one, it searches for the dual experiences of the researcher as the artist as the instrument who producing the drawing and as the spectators himself welcoming and appreciating as he/she reveals him/ herself capable of wondering. In a particular way, this research is to show that through the making of drawings, the drawing performs lived-experience, that it can be another paradigm so called art-based or artistic research.